2019
DOI: 10.1038/s41598-019-44593-6
|View full text |Cite
|
Sign up to set email alerts
|

Human osteogenic differentiation in Space: proteomic and epigenetic clues to better understand osteoporosis

Abstract: In the frame of the VITA mission of the Italian Space Agency (ASI), we addressed the problem of Space osteoporosis by using human blood-derived stem cells (BDSCs) as a suitable osteogenic differentiation model. In particular, we investigated proteomic and epigenetic changes in BDSCs during osteoblastic differentiation induced by rapamycin under microgravity conditions. A decrease in the expression of 4 embryonic markers (Sox2, Oct3/4, Nanog and E-cadherin) was found to occur to a larger extent on board the ISS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Role of miR-494 in the defect of osteogenesis (Qin et al, 2019). Effect of rapamycin in osteogenic differentiation (Gambacurta et al, 2019).…”
Section: Vesselsmentioning
confidence: 99%
“…Role of miR-494 in the defect of osteogenesis (Qin et al, 2019). Effect of rapamycin in osteogenic differentiation (Gambacurta et al, 2019).…”
Section: Vesselsmentioning
confidence: 99%
“…The Guest Edited Collection ‘ Gravitational biology and space medicine ’ includes publications reporting on health concerns for astronauts and cosmonauts 1416 during space missions, and physiological changes caused by short-term µ g 17 . Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 . Moreover, cell studies in simulated (s-) µ g at ground-based facilities are included in this Collection 2630 .…”
mentioning
confidence: 99%
“…Gambacurta et al . 24 showed that rapamycin induces transcriptional activation of human blood-derived stem cells (BDSCs) towards osteogenic differentiation in space. These findings, applying proteomics and epigenetic methods, may represent the first step in identifying new biomarkers and therapeutic targets to treat osteoporosis in space and on Earth 24 .…”
mentioning
confidence: 99%
“…Current exploration medical capabilities are particularly vulnerable to this paradigm shift. The list of necessary supplies to address persistent exposures of space travel adds up quickly: includ ing countermeasures for increased radiation 3,4 , bone loss 5,6 , kidney stones 7,8 , vision impairment 9 , and adverse behavioral conditions 10 to name a few. The list of supplies begins to look unmanageab le when you add in intermittent, or even unanticipated, exposures such as microbial infection [11][12][13] , and implications of spaceflight-induced genome instability and metabolic changes 14 .…”
Section: Re-thinking Human Health For Deep Space Missionsmentioning
confidence: 99%